EVALUATION OF INSECTICID ACTIVITY OF LANTANA CAMARA ON RED FLOUR BEETLE (TRIBOLIUM CASTANIUM) CAUSING DAMAGE ON WHEAT IN THE STORAGE - Abba, M.; Aliyu, M.; Tijjani A.; Zaharaddeen, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
Laboratory experiment was carried out to determine the insecticidal activity of leaves and root powder of Lantana camara and optimum concentration for the management of Red Flour Bettle (Tribolium castanium). Actellic dust was used as positive control while untreated wheat seeds serving as negative control. The consisted of three rates of Leaf powder (1.5 g, 3.5 g and 5.5 g), three rates of root powder (1.5 g 3.5 g and 5.5 g), Actellic dust and a control These were applied to 100 g uninfested wheat seedslaid out in a Completely Randomized Design (CRD) andrepeated three times. Contact activity of the plant products were evaluated and data collected were subjected to analysis of variance (ANOVA) and means were separated using NDMRT at 1% and 5% probability level. Five pairs of laboratory reared F2 generation of the T. castanium was introduced into the treated and untreated wheat The open end of the plastic containers was covered with a fine muslin cloth and tied firmly with rubber band and kept at room temperature (29 – 32oC) in the laboratory. Observation on insect mortality was recorded at 24, 48and 72 hours after exposure to the treatment for three days. The results showed thatapplication of 5.5 g/100g leaves powders significantly (P≤0.05) caused highest mortality of adult T. castanium at 24 (3.00), 48 (2.67), 72 (2.00) and 96 (2.00) hours by contact toxicity compare to other treatments. Similarly, wheat seeds treated with 5.5 g /100 g of the leaves and root powder significantly (P≤0.05) decreased Oviposition (0.00), Adult emergence (0.00), Percentage grain damage (4.33%), Number of exit holes (0.00) and Weight loss (0.00%). Germination of the treated seeds was not affected negatively. The 5.5 g and 3.5 of leave of L. camara could be recommended as an alternative to chemical insecticides to be used as contact protectants against T. castanium on stored wheat seeds.